Pengaruh Gaya Kepemimpinan, Komunikasi, Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Guru di MAN 1 Rembang - Agus Merdeka Kusuma Rahayu; Syaiko Rosyidi (Jurnal Riset Akuntansi Politala, 2026)
The aim of this study is to test and analyze the influence of leadership style, communication, work motivation, and work environment on the performance of MAN 1 Rembang teachers. By using a quantitative approach and applying a saturated sampling method involving the entire population, namely 39 civil servant and PPPK teachers at MAN 1 Rembang as informants. Information data were obtained by distributing questionnaires and analyzed using multiple linear regression techniques and assisted by the IBM SPSS version 25 application. These findings reveal that leadership style has a significant negative effect on teacher performance, communication and work motivation both have a significant positive impact on teacher performance, on the other hand the work environment shows a positive but insignificant output on teacher performance.